Hydrochemistry and mobilization of gold in the hypergenesis zone (Kuznetsk Alatau, Russia); Geology of Ore Deposits; Vol. 43, iss. 3 - Shvartsev S. L. Stepan Lvovich (2001, 2001)
В фонде НТБ ТПУ отсутствует